'Working Together': An Intercultural Academic Leadership Programme to Build Health Science Educators' Capacity to Teach Indigenous Health and Culture. Issue 1 (10th June 2016) - Durey, Angela; Taylor, Kate; Bessarab, Dawn; Kickett, Marion; Jones, Sue; Hoffman, Julie; Flavell, Helen; Scott, Kim
Abstract : Progress has been slow in improving health disparities between Aboriginal and Torres Strait Islander (Indigenous) Australians and other Australians. While reasons for this are complex, delivering healthcare respectful of cultural differences is one approach to improving Indigenous health outcomes. This paper presents and evaluates an intercultural academic leadership programme developed to support tertiary educators teaching Indigenous health and culture prepare interdisciplinary students to work respectfully and appropriately as health professionals with Indigenous peoples. The programme acknowledges the impact of colonisation on Indigenous Australians and draws on theories of the intercultural space to inform reflection and discussion on Indigenous/non-Indigenous relations and their impact on healthcare. Furthermore, the programme encourages establishing a community of practice as a resource for educators. Evaluation indicated participants' confidence to teach Indigenous content increased following the programme. Participants felt more able to create intercultural, interdisciplinary and interactive learning spaces that were inclusive and safe for students from all cultures. Participants learned skills to effectively facilitate and encourage students to grapple with the complexity of the intercultural space, often tense, uncertain and risky, to enable new understandings and positions to emerge that could better prepare graduates to work in Indigenous health contexts.